Tailoring the porosity of ZnO/ZnFe2O4 composites for photocatalytic applications. Issue 17 (1st December 2017) - Chen, Mansheng; Liu, Dongcheng; Deng, Yifang; Fu, Weiwei; Zou, Huahong; Liang, Fupei
Abstract: This paper reported a novel method to synthesize porous ZnO/ZnFe2 O4 particles by chemically etching ZnO/ZnO2 O4 /SO2 composite particles in an alkaline solution, and the porosity of the particles could be tailored by controlling the concentration of SO2 in the ZnO/ZnO2 O4 /SO2 composites. The photocatalytic performance of both solid and porous ZnO/ZnFe2 O4 particles was investigated in methylene blue (MB) degradation reaction. The results showed that the particles with higher porosity displayed a higher catalytic performance, which was indicated by a larger first-order reaction constant (κ) and an improved degradation efficiency (η). Moreover, the magnetization of the particles could be used for the magnetic separation of catalysts after reactions.